The effect of political skill among employees towards stakeholders’ satisfaction : A study on Iskandar Malaysia / Amira Afiqa Jasni - Jasni, Amira Afiqa (Faculty of Business and Management, 2018)
This study is conducted at Iskandar Regional Development Authority Sdn. Bhd. commonly known as Iskandar Malaysia. The main objective of this project paper is to identify the influence of dimension of political skill toward stakeholders‟ satisfaction. The independent variables of this study consist of four dimensions under political skill which are social astuteness, networking ability, interpersonal influence and apparent sincerity. While, the dependent variable of this study is stakeholders’ satisfaction.